Atlas of Pediatric Hepatology (Springer International Publishing, 2018)
This atlas is a problem-based practical book presenting clinical scenarios for children with liver disease. Each chapter demonstrates the clinical presentation, diagnostic pathway, therapy and outcome. Rich in illustrations of clinical pictures, tables and graphs of data, each chapter also contains pictures of radiology, histopathology and other important diagnostic information. This book outlines a multidisciplinary approach to diagnosis and management of pediatric liver disease and covers diseases encountered in South Asia, the Far East and the Middle East. This work will appeal to a wide readership, from trainees in hepatology and Paediatric Gastroenterology to General Paediatricians and Allied Health Professionals including Dieticians, Nurses, Transplant Co-Ordinators.